PENGARUH KEPERCAYAAN DIRI TERHADAP KETERAMPILAN BERBICARA BAHASA INGGRIS PADA MAHASISWA TADRIS BAHASA INGGRIS - Azizah Mardatillah (EDUCATIONAL JOURNAL : General and Specific Research, 2024)
Language is very important in communication. Language becomes one of the foundations for achieving success in creating good communication. Therefore, skills in using languages are very influential and become a special concern in language learning. Speaking is part of English lessons both at the elementary level to the college level at the moment. The development and acceleration of technology also requires everyone to be able to communicate and speak internationally, in this case English well and smoothly. However, there are some barriers to applying English language skills especially to students at a college. The factor of confidence and courage is a student’s self-image in implementing the ability to speak English in the classroom and the surrounding environment. While in the assessment of English speaking skills, students need to have vocabulary knowledge, grammar, fluency, accents, and understanding. The aim of this study is to analyze and know the relationship of confidence with English speaking skills in students of the 4th semester of Tadris English. The research method used is Qualitative Descriptive using survey data to students of the 4th semester of English.